Characterisation of the telomeres at opposite ends of a 3 Mb Theileria parva chromosome - Sohanpal, B.K.; Morzaria, S.P.; Gobright, E.I.; Bishop, Richard P. (Oxford University Press, 1995)
Bacteriophage clones containing Theileria parva genomic DNA derived from two different telomeres were isolated and the nucleotide sequences of the telomeric repeats and adjacent telomere-associated (TAS) DNA were determined. The T. parva telomeric repeat sequences, a tandem array of TTTTAGGG or TTTAGGG interspersed with a few variant copies, showed a high degree of sequence identity of those of the photosynthetic algae Chlamydomonas reinhardtii (97 percent identity) and Chlorella vulgaris (87.7 percent identity) and the angiosperm Arabidopsis thaliana (84.4 percent identity). Unlike most organisms which have been studied, no significant repetitive sequences were found in the nucleotide sequences of TAS DNA located centromere-proximal to the telomeric repeats. Restriction mapping and hybridisation analysis of EMBL3 clones containing 16 kilobases of TAS DNA derived from one telomere suggested that they did not contain long regions of repetitive DNA. The cloned TAS DNAs were mapped to T. parva muguga genomic SfiI fragments 8 and 20, which are located at opposite ends of the largest T. parva chromosome. A 126 bp sequence located directly centromere-proximal to the telomeric repeats was 94 percent identical between the two cloned telomeres. The conserved 126 bp sequence was present on all T. parva Muguga telomeric SfiI fragments.